1994
DOI: 10.1111/j.1365-2133.1994.tb02906.x
|View full text |Cite
|
Sign up to set email alerts
|

Juvenile dermatomyositis: treatment with intravenous gammaglobulin

Abstract: High-dose intravenous gammaglobulin (IVGG) has proved to be effective in the treatment of a number of immune disorders. We report two patients with juvenile dermatomyositis (DM) who improved with IVGG therapy. These patients had become refractory to corticosteroids and had developed unacceptable steroid toxicity. We suggest that IVGG can be useful in the treatment of juvenile DM, by reducing steroid requirements, and replacing immunosuppressive drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

1995
1995
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(15 citation statements)
references
References 6 publications
0
13
0
1
Order By: Relevance
“…IVIG has been used in the treatment of JDM since the 1980s as reported in case reports and small case series. The majority of reported patients experienced improvement in skin disease and muscle strength, and the use of IVIG also reduced the cumulative glucocorticoid dose in most patients [85][86][87][88]. In 2011 a large retrospective study including 78 JDM patients confirmed the efficacy of IVIG in controlling JDM disease activity, particularly for steroid resistant patients [89].…”
Section: Intravenous Immunoglobulins (Ivig)mentioning
confidence: 99%
“…IVIG has been used in the treatment of JDM since the 1980s as reported in case reports and small case series. The majority of reported patients experienced improvement in skin disease and muscle strength, and the use of IVIG also reduced the cumulative glucocorticoid dose in most patients [85][86][87][88]. In 2011 a large retrospective study including 78 JDM patients confirmed the efficacy of IVIG in controlling JDM disease activity, particularly for steroid resistant patients [89].…”
Section: Intravenous Immunoglobulins (Ivig)mentioning
confidence: 99%
“…[13][14][15][16][17][18][19][20][21][22][23][24] In 1993, Dalakas et al 25 reported the efficacy of IVIG in a doubleblind, placebo-controlled study for DM. We conducted a prospective study to assess the efficacy of IVIG for steroidresistant PM/DM in Japan.…”
Section: Introductionmentioning
confidence: 99%
“…Gastrointestinal disturbance, anorexia, fatigue, stomatitis, and alopecia are the most commonly reported adverse effects. [57][58][59][60] Additionally, a case of adult-onset amyopathic DM refractory to corticosteroid therapy responded to low-dose (10% of the standard dose of 1 mg kg day) IVIG. Renal impairment and pulmonary toxicity are also reported.…”
Section: Other Systemic Therapiesmentioning
confidence: 99%